THE STATUS OF WOMEN IN THE SAFAVID STATE: POLITICAL, SOCIAL, AND MILITARY AGENCY DURING THE FORMATIVE PERIOD (1501–1576) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the social, political, and military standing of Qizilbash-Turkmen women during the formative decades of the Safavid state (1501–1736), with particular attention to the reigns of Shah Ismail I (r. 1501–1524) and his successor Shah Tahmasp I (r. 1524–1576). Drawing on a comparative reading of Safavid court chronicles (Alam-ara-yi Safavi, Khulasat al-Tawarikh, Jawahir al-Akhbar) alongside the observations of European travelers and diplomats — Michele Membré, Caterino Zeno, and the Carmelite missionary Pietro della Valle's circle — the study reconstructs the political biography of Taclı Begüm, principal consort of Shah Ismail I, from her documented presence at the Battle of Chaldiran (1514) through her influential role after Ismail's death and her eventual banishment under Tahmasp. The inquiry situates this trajectory within the wider Turkic-Turkmen "alp kadın" (heroic woman) archetype attested in Oghuz epic literature and within the complementary gender cosmology of Alevi-Bektashi belief, arguing that female political and military visibility in the early Safavid polity was not incidental but structurally embedded in Qizilbash-Turkmen culture. The article further shows that Tahmasp's religious reorientation toward juristic Twelver Shiism, propelled by the arrival of Arab Shia scholars from Jabal Amil, initiated a systemic contraction of women's public agency that only partially eased under Shah Abbas I (r. 1588–1629). The findings contribute to Safavid historiography, gender and Islamic studies, and Central Asian cultural history.
Keywords: Safavid state; Qizilbash-Turkmen; Taclı Begüm; alp kadın (heroic woman); Shah Ismail I; Shah Tahmasp I; Battle of Chaldiran; Alevi-Bektashi tradition; gender and statecraft.